Association of Prior to Intensive Care Unit Statin Use With Outcomes on Patients With Acute Kidney Injury - Tu, Boxiang; Tang, Yuanjun; Cheng, Yi; Yang, Yuanyuan; Wu, Cheng; Liu, Xiaobin; Qian, Di; Zhang, Zhansai; Zhao, Yanfang; Qin, Yingyi; He, Jia (Frontiers in Medicine, 2021)
Purpose: To evaluate the association of prior to intensive care unit (ICU) statin use with the clinical outcomes in critically ill patients with acute kidney injury (AKI). Materials and Methods: Patients with AKI were selected from the Medical Information Mart for Intensive Care IV v1.0 database for this retrospective observational study. The primary outcome was 30-day ICU mortality. Thirty-day in-hospital mortality and ICU length of stay (LOS) were considered as secondary outcomes. Comparison of mortality between pre-ICU statin users with non-users was conducted by multivariable cox proportional hazards model. Comparison of ICU LOS between two groups was implemented by multivariable linear model. Three propensity score methods were used to verify the results as sensitivity analyses. Stratification analyses were conducted to explore whether the association between pre-ICU statin use and mortality differed across various subgroups classified by sex and different AKI stages. Results: We identified 3821 pre-ICU statin users and 9690 non-users. In multivariable model, pre-ICU statin use was associated with reduced 30-day ICU mortality rate [Hazard ratio (HR) 0.68 (0.59,0.79); P<0.001], 30-day in-hospital mortality rate [HR 0.64 (0.57, 0.72); P<0.001] and ICU LOS [Mean Difference -0.51(-0.79, -0.24); P<0.001]. The results were consistent in three propensity score methods. In Subgroup analyses, pre-ICU statin use was associated with decreased 30-day ICU mortality and 30-day in-hospital mortality in both sexes and AKI stages, except for 30-day ICU mortality in AKI stage 1. Conclusions: Patients with AKI who were administered statins prior to ICU admission might have lower mortality during ICU and hospital stay and shorter ICU LOS.